Exceptions and paths: occupations as event and experience in Brazil of our time - Rebuá, Eduardo (2017)
An insight about culture, politics and educational articulations in the present brazilian scene means the dealing with cathegories, and concepts but above all the ontological and ethic colors which if not representing micro photos of the whole allows us to understand the real synthesis of several processes and feelings to offer a more accurate analysis and concrete approaching of some of the most significant phenomena of contemporary Brazil.In this movement searching for new political feeling structures, even though mixed with old resistance morphologies, to understand to what extent the growing since Junho (2013), occupations of schools and public universities aswell as urban spaces, mainly by the homeless, show questions, experiences and material knowledges, as symbolic procedures able to mobilize outstanding intelectual people including social fights not only from the comfort/certainty but also  from the moving and mobilizations produced by political-pedagogic procedures.Our theoric-metodologic-analytic basis remains, after all, on historic materialism contribution with double articulation: the concept of eventin Zizek and the concept of experience in Benjamim (Erfahrung), aiming to undersrtand the occupations as political paths under circunstances of exceptions.